2019
DOI: 10.1021/acsami.9b07115
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Ethane Selectivity in Ethane–Ethylene Mixtures by Perfluoro Groups in Zr-Based Metal-Organic Frameworks

Abstract: A series of zirconium dicarboxylate-based metal-organic frameworks (Zr MOFs) of the UiO-66 (tetrahedral and octahedral cages) or MIL-140 (triangular channels) structure type were investigated for the separation of ethane/ethylene mixtures. The adsorption, investigated both experimentally and computationally, revealed that the size and type of pores have a more pronounced effect on the selectivity than the aromaticity of the linker. The increase in pore size when changing from benzene to naphthalene (NDC) dicar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 51 publications
(90 reference statements)
3
66
0
Order By: Relevance
“…As it was already pointed out, the inversed C 2 H 6 /C 2 H 4 adsorption selectivity is a rather unusual phenomenon. The corresponding selectivity factors for MOFs reported up to now at ambient conditions are typically quite low ( S <3) with MAF‐49 being the only exception with appreciable selectivity S =9.0 [22, 28–34, 42–55] . The best C 2 H 6 /C 2 H 4 absorption selectivity obtained for NIIC‐20‐Bu at similar conditions ( S =15.4) is 1.7 times higher than that for MAF‐49 and greatly surpasses the majority of other literature results reported so far (Table S9).…”
Section: Resultsmentioning
confidence: 39%
See 1 more Smart Citation
“…As it was already pointed out, the inversed C 2 H 6 /C 2 H 4 adsorption selectivity is a rather unusual phenomenon. The corresponding selectivity factors for MOFs reported up to now at ambient conditions are typically quite low ( S <3) with MAF‐49 being the only exception with appreciable selectivity S =9.0 [22, 28–34, 42–55] . The best C 2 H 6 /C 2 H 4 absorption selectivity obtained for NIIC‐20‐Bu at similar conditions ( S =15.4) is 1.7 times higher than that for MAF‐49 and greatly surpasses the majority of other literature results reported so far (Table S9).…”
Section: Resultsmentioning
confidence: 39%
“…The corresponding selectivity factors for MOFs reported up to now at ambient conditions are typically quite low (S < 3) with MAF-49 being the only exception with appreciable selectivity S = 9.0. [22,[28][29][30][31][32][33][34][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Theb est C 2 H 6 /C 2 H 4 absorption selectivity obtained for NIIC-20-Bu at similar conditions (S = 15.4) is 1.7 times higher than that for MAF-49 and greatly surpasses the majority of other literature results reported so far (Table S9). Other than the adsorption selectivity,the adsorption uptake is an equally important parameter for an adsorbent for gas separation applications.I nt his regard, am ore accurate evaluation of porous materials should be revealed from the selectivity vs.uptake plot.…”
Section: Forschungsartikelmentioning
confidence: 69%
“…First-principle based hybrid density functional theory (DFT) was used to perform all the computations. [29][30][31][32][33] It is essential to include the long-range dispersion correction in the hybrid DFT [30][31][32][33][34][35][36][37][38][39][40][41][42] to describe the systems properly, as there are many weak van der Waals interactions in MOF model systems. The improved version of semi-empirical Grimme-D3 (ref.…”
Section: Computational Details and Methodologymentioning
confidence: 99%
“…Recently, Pinto et al reported UiO-66 (Zr)-CF 3 as an ethane-selective adsorbent over ethylene. 25 This is the first report that a porous material having a fluorine functional group exhibits a preference for ethane over ethylene.…”
mentioning
confidence: 95%
“…For the ethane-selective MOFs and porous carbons, the interactions between the adsorbent and ethane, derived from C─HÁÁÁπ, CHÁÁÁN/O, and C─HÁÁÁF have been claimed as a driving force for selective ethane adsorption in porous materials. [21][22][23][24][25][26][27] Fluorine has the advantage of forming a strong hydrogen bond via interaction with the most electronegative fluorine and electro-deficient hydrogen. 28 The use of a MOF having a fluorine functional group, which can be easily synthesized from a fluorine-functionalized organic ligand and a metal precursor, can be an effective approach.…”
mentioning
confidence: 99%